2002
DOI: 10.1002/ddr.10083
|View full text |Cite
|
Sign up to set email alerts
|

Metal ion chelation in neurodegenerative disorders

Abstract: Disturbance in metallochemical reactions and metal‐protein association are associated with chronic neurodegenerative conditions, such as Alzheimer's and Parkinson's disease, as well as with neurodegeneration triggered by acute cerebral ischaemia. Many neurological diseases have been linked directly or indirectly to perturbed homeostasis of Ca, Fe, Zn, or Cu ions. Consequently, acute or chronic neurodegenerative disorders represent excellent targets for exploiting metal ion chelator approaches. Drug Dev. Res. 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
51
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 62 publications
3
51
0
Order By: Relevance
“…13 The membrane-activated, zinc-specific chelating agent DP-b99 was postulated to offer neuroprotective or neurorestorative effects in experimental stroke. [13][14][15][16] DP-b99 seemed well tolerated by patients with acute stroke, and a phase IIb trial reported better outcomes among DP-b99-treated patients than a control group on a secondary outcome measure. 17 Post hoc subgroup analysis suggested that the greatest intergroup difference was present among patients with stroke of moderate severity (National Institutes of Health Stroke Scale [NIHSS] 10 to 16) who had features suggestive of cortical damage.…”
mentioning
confidence: 99%
“…13 The membrane-activated, zinc-specific chelating agent DP-b99 was postulated to offer neuroprotective or neurorestorative effects in experimental stroke. [13][14][15][16] DP-b99 seemed well tolerated by patients with acute stroke, and a phase IIb trial reported better outcomes among DP-b99-treated patients than a control group on a secondary outcome measure. 17 Post hoc subgroup analysis suggested that the greatest intergroup difference was present among patients with stroke of moderate severity (National Institutes of Health Stroke Scale [NIHSS] 10 to 16) who had features suggestive of cortical damage.…”
mentioning
confidence: 99%
“…In the present study, which included only patients with cortical involvement and thus, those most likely with large hemispheric infarcts, the dose used (1 mg/kg per day) was 2 to 3 orders of magnitude higher than that used in preclinical in vivo studies. 7 Previous exposure of healthy volunteers and stroke patients to repeated DP-b99 administrations of 1 mg/kg per day have shown this dose to be safe. 10,11 In an earlier small-scale study of this dose administered to acute stroke patients for 2 consecutive days (with a treatment window of 12 hours), a larger decrease from baseline on the National Institutes of Heath Stroke Scale (NIHSS) was observed with DP-b99 compared with placebo after a 30-day follow-up.…”
mentioning
confidence: 99%
“…6 DP-b99 is a membrane-activated lipophilic chelator of divalent metal ions that is designed to chelate these ions only in the vicinity of membranes and when their concentrations exceed physiologic levels, thus affecting the function of proteins that require these ions for their activation. 7 In cellular systems, DP-b99 has been shown to atten-uate detrimental zinc-dependent membrane-associated processes, such as calpain activation and tumor necrosis factor-␣-induced activation of matrix metalloproteinase-9. 7 In rodent models of cerebral ischemia, DP-b99 therapy reduced infarct volume and neuron-specific enolase release and increased the survival rate.…”
mentioning
confidence: 99%
See 2 more Smart Citations